2017
DOI: 10.1007/s11060-017-2682-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cerebellar glioblastomas in adults

Abstract: Adult cerebellar glioblastomas (cGBM) are rare and their characteristics remain to be fully described. We analyzed the characteristics of 17 adult patients with cGBM and compared them to a series of 103 patients presenting a supra-tentorial glioblastoma (stGBM). The mean age at GBMc diagnosis was 53.4 years (range 28-77). A history of neurofibromatosis type I was noted in 3 patients. cGBM were hemispheric in 10 patients (58.8%), only vermian in 4 patients (23.5%), and both vermian and hemispheric in 3 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
3
25
0
1
Order By: Relevance
“…In addition, we identified a significantly higher rate of cerebellar GBM in the TERT p-wt compared with the TERT p mutant patients. Our finding is consistent with prior studies that have shown that cerebellar GBMs occur in patients that are younger than patients with supratentorial GBMs, and have decreased frequency in TERT p mutations and more frequent NF1 mutations [ 16 , 20 ]. Taken together with our findings, these data support the proposal that cerebellar GBMs may comprise a distinct subclass of tumor, which may arise via an alternative molecular etiology when compared to supratentorial TERT p mutant GBM.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we identified a significantly higher rate of cerebellar GBM in the TERT p-wt compared with the TERT p mutant patients. Our finding is consistent with prior studies that have shown that cerebellar GBMs occur in patients that are younger than patients with supratentorial GBMs, and have decreased frequency in TERT p mutations and more frequent NF1 mutations [ 16 , 20 ]. Taken together with our findings, these data support the proposal that cerebellar GBMs may comprise a distinct subclass of tumor, which may arise via an alternative molecular etiology when compared to supratentorial TERT p mutant GBM.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, a total of nine studies were included for meta-analyses comprising of 2819 glioma patients ( Fig. 1) [16,[25][26][27][28][29][30][31][32]. The baseline characteristics of these studies were presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Signatures predictive of aggressive clinical behavior will not apply to most pediatric diffuse gliomas and may not be relevant to diffuse gliomas arising in other less common sites. For example, IDH-wildtype diffuse astrocytic gliomas that arise in the cerebellum of adults are rare, and recent studies indicate that they do not harbor the same percentage of EGFR amplification, +7/−10, or TERT promoter mutations as their supratentorial counterparts[22, 23]. A subset will harbor H3 K27 or SETD2 mutations, but the full spectrum of their other alterations have not been defined, nor have the genetic events corresponding to aggressive behavior.…”
Section: Caveatsmentioning
confidence: 99%